Contrasting Roles of a Large Alpine Lake on Tibetan Plateau in Shaping Regional Precipitation During Summer and Autumn - Dai, Yufeng; Yao, Tandong; Wang, Lei; Li, Xiangyu; Zhang, Xiaowen (Frontiers in Earth Science, 2020)
Lakes have important influence on local temperature and precipitation and are also regulators of regional climate. Using satellite and climate reanalysis datasets and a regional weather research forecasting (WRF) model, we carried out two WRF sensitivity experiments: one including the lake (WRF_lake) and the other with lake replaced by land surface (WRF_nolake). The comparison between the two sensitivity WRF experiments revealed that, in summer, the lake was strong heat sink in the daytime and heat source at night. In contrast, in autumn, the lake was heat sink in the daytime and strong heat source at night. Correspondingly, the precipitation was reduced by about 45–70% over the lake because of the cooling effect in summer of 2008, and the precipitation over the lake and to the east of the lake was enhanced by 60% because of the warming effect of 2008.